KESEHATAN PERBANKAN SEBAGAI INFORMASI PENETAPAN SUKU BUNGA PENJAMINAN LPS - OKTAVIANTI, FLORIANA (Universitas Katolik Widya Mandala Surabaya, 2013)
This study aimed to test the feasibility of deposit insurance’s policy in determining insurance interest rate imposed on go public’s banks. The test is performed by calculating the bank's performance by using CAMEL ratio (CAR, APB, PPAP, ROA, ROA and LDR) to obtain bank performance ratings were then tested for differences using One Sample T-Test Statistic. This study uses secondary data by the number of samples used by 31 banking companies listed on the Indonesia Stock Exchange for a period of 3 years 2009-2011. The results showed that the performance of banking is no different in the case of banks listed on the Indonesian Stock Exchange. This proves that deposit insurance has the right policies in determining the interest rate guarantee is flat.